RASIO NEUTROFIL LIMFOSIT PADA PASIEN DEMAM TIFOID DI RUMAH SAKIT ISLAM SITI RAHMAH PADANG TAHUN 2023 - Anggraini, Debie; Nirmala, Nirmala; Rahma Triyana (Yayasan Nusantara Hasana Berdikari, 2025)
Typhoid fever is an acute infection caused by Salmonella typhi, primarily occuring in developing countries, this condition can be diagnosed in various ways, one of which is through the neutrphil-lymphocyte-rasio (NLR) as an indikator of body inflammation. This study aims to assess the NLR typhoid fever patients at Siti Rahmah Islamic Hospital, Padang in 2023, as well asthe distribution based on age, gender, body temperature, and patient outcomes. This study employed a descriptive observational method with a cross-sectional design. Data were obtained from the medical records of typhoid fever patients who underwent at the hospital 2023. The sample was taken using a total sampling method, involving 29 patients. The study involved 29 typhoid fever patients, the majority of whom were female (65,5%) andn most commonly aged 0-5 years (44,8%). Most patients exhibited neutophilia (>70%) at 89,7% and lymphocytopenia (<20%) at 86,2%. The mean NLR value was 6,32, indicating inflammation. Most patients had febrile body temperature (38-39,9°C) at 65,5%. Based on the tubex scale 55,2% of patients had values greater than 6, indicating a strong likelihood of typhoid infection. A total of 65,5% of patients showed improvement after treatment. The NLR indicates an increas in neutrophil rasio and decrease un lymphocytes in typhoid fever patients. This study emphasizes the importance of NLR examination as supporting diagnositic tool and clinical management of typhoid fever.